Bacteriocin production by mucosal bacteria in current and previous colorectal neoplasia - Kohoutova, Darina; Forstlova, Miroslava; Moravkova, Paula; Cyrany, Jiri; Bosak, Juraj; Smajs, David; Rejchrt, Stanislav; Bures, Jan (BMC cancer, 2020)
BACKGROUND: Optimal therapy for colorectal carcinoma (CRC), a frequently diagnosed malignancy, does not exist. Some of colicins and microcins, ribosomally synthesized peptides by gramnegative bacteria, have shown significant biological activity specifically against different cancer cells in vitro and in vivo conditions. The aim of this prospective study was to evaluate natural colicin and microcin production by large intestinal mucosal bacteria in each stage of colorectal neoplasia and in those with a history of colorectal neoplasia. METHODS: A total of 21 patients with non-advanced adenoma (non-a-A; 16/21 with current and 5/21 with history of non-a-A), 20 patients with advanced colorectal adenoma (a-A; 11/20 with current and 9/20 with history of a-A), 22 individuals with CRC (9/22 with current and 13/22 with history of CRC) and 20 controls were enrolled. Mucosal biopsies from the caecum, transverse colon and the rectum were taken during colonoscopy in each individual. Microbiological culture followed. Production of colicins and microcins was evaluated by PCR methods. RESULTS: A total of 239 mucosal biopsies were taken. Production of colicins and microcins was significantly more frequent in individuals with non-a-A, a-A and CRC compared to controls. No significant difference in colicin and microcin production was found between patients with current and previous non-a-A, a-A and CRC. Significantly more frequent production of colicins was observed in men compared to women at the stage of colorectal carcinoma. A later onset of increased production of microcins during the adenoma-carcinoma sequence has been observed in males compared to females. CONCLUSIONS: Strains isolated from large intestinal mucosa in patients with colorectal neoplasia produce colicins and microcins more frequently compared to controls. Bacteriocin production does not differ between patients with current and previous colorectal neoplasia. Fundamental differences in bacteriocin production have been confirmed between males and females.
Keywords: Male; kolorektální nádory; Colorectal carcinoma; Microcin; Bacteria; biopsie; střevní sliznice; Gastrointestinal Microbiome; mužské pohlaví; střevní mikroflóra; Bacteriocins; bakteriociny; lidé; Gramnegative bacteria; ženské pohlaví; Colicin; Colorectal neoplasia; Humans; Intestinal Mucosa; Colorectal Neoplasms; Biopsy; Female